2002
DOI: 10.1177/154193120204601208
|View full text |Cite
|
Sign up to set email alerts
|

Task Context and Individual Difference Effects on Skill Acquisition of Visual Processing Strategy

Abstract: Pratt and Sohn (2001) suggested that training context impacts those with a holistic strategy while training context does not influence transfer performance for those with an analytic strategy. The present research attempts to compliment and extend their findings by examining the role of complexity and how it interacts with individual differences in visual processing strategy. Participants were given a visual discrimination task in which they trained on one of four stimulus sets that varied in complexity and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Training content interacts with cognitive styles to influences strategy development and subsequent performance in transfer tasks (Kramer et al, 2002;Kramer et al 2003;Pratt & Sohn, 2001). Individuals screened as having an analytic cognitive style performed equally well on a transfer task regardless of training content.…”
Section: Training Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Training content interacts with cognitive styles to influences strategy development and subsequent performance in transfer tasks (Kramer et al, 2002;Kramer et al 2003;Pratt & Sohn, 2001). Individuals screened as having an analytic cognitive style performed equally well on a transfer task regardless of training content.…”
Section: Training Contentmentioning
confidence: 99%
“…Individuals with a holistic cognitive style performed as well as the analytic group only when trained with difficult to discriminate, or similar-appearing, stimulus sets than when trained with easy to discriminate, or dissimilarappearing stimulus sets. Kramer et al (2002) suggested that differences between analytic and holistic transfer performance were due to strategy development during initial training. When given difficult training, the holistic group had to modify their preferred style of visual discrimination in order to see minuscule differences by using a point-by-point comparison approach.…”
Section: Training Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, any difference in accuracy performance between groups would be due to a more efficient strategy of discriminating stimuli. Cooper's (1976) methodology (Doane et al, 19%;Kramer et al, 2002;Pratt and Sohn, 2001).…”
Section: Reaction Timementioning
confidence: 99%
“…One approach to interface design is to take into account individual differences in visual search strategies. Previous research has shown when searching computer graphics, individuals who differ in visual search strategies perform equally well if provided appropriate training (Doane, Alderson, Sohn, & Pellegrino, 1996;Doane, Sohn & Schreiber, 1999;Pratt & Sohn, 2001;Kramer, Pratt, &Sohn, 2002). It is uncertain whether these results can be replicated using the emblematic stimuli associated with a pilot interface.…”
Section: Introductionmentioning
confidence: 98%